A CONTINUITY ANALYSIS OF INDEPENDENT NURSING CARE DOCUMENTATION USING THE FISHBONE DIAGRAM IN THE TERATAI ROOM NORTH 2ND FLOOR X HOSPITAL, JAKARTA: DOI: https://doi.org/10.35654/ijnhs.v2i1.81 - Martha Evi Tondang (Alta Dharma Publisher, 2019)
Quality nursing care documentation based on facts, accurate, complete, concise, organized, timely, easy to read, and continuity. Continuity of nursing care is fulfilled if the range of health services is appropriate, the availability of quality caregivers professionals and information related to patient care are delivered on an ongoing basis. The method used is a case study with observation, interviews, secondary data and document review. This study that is an innovation project, uses a fish bone diagram approach to identify the causes of the discontinuity independent nursing care documentation. Documentation of evaluation of independent nursing care for the development of patients in the midwifery and ginecology room in X Hospital in Jakarta has not reflected the continuity of nursing care. The causes include the lack of optimal competence in providing independent nursing care, not optimal nursing manager functions. The continuity is overcome by optimizing the nursing manager's function by making SOP note integrated patient development, revision of midwife's job description, revision of guide to nursing practice, electronic-based documentation system, placing midwives in accordance with the service area the authority and standard of the profession, the structured supervision schedule, and make sure the midwife's job description is in accordance with the policy.